Relationship between Fiscal Deficit and Public Debt in Nigeria: an Error Correction Approach - Folorunso, Benjamin Ayodele (Journal of Economics and Behavioral Studies, 2013)
The paper examined the nexus between fiscal deficit and public debt in Nigeria. Public debt was disaggregated into domestic and external debt with a view to analyzing the causal relationship and relative effect of both categories of debt on fiscal deficit. Time series data were collected from Statistical Bulletins published by the Central Bank of Nigeria from 1970 to 2011. Except for inflation rate that was I(0), the unit root test results revealed stationarity of fiscal balance, public debt and its components, income, exchange rate and rate of interest series at their first difference; they are I(1) series. Pair-wise Granger causality results support bi-directional relationship between fiscal balance and public debt as well as its domestic component while causality run only from external debt to fiscal deficit. Johansen cointegration results also confirmed the existence of cointegrating relationships at 5 per cent level of significance. In addition, error correction estimates revealed that fiscal balance had significant positive relationship with debt in Nigeria in both the short and long run. The results showed that 1 per cent increase in public debt resulted in an increase of 1.85 per cent in fiscal deficit. In addition, 1 per cent increase in fiscal deficit resulted into 0.08 per cent increase in public debt. The paper further confirmed that domestic debt has greater impact on fiscal deficit than external debt. The paper concluded that the Nigerian government should consider appropriate mix of domestic debt and external debt as a mean of financing budget deficit.